Development of Cybathletics: Integration of Autogenic Training - Kardanov, V.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the impact of using self-regulation methods (autogenic training, visualization, breathing techniques) on the emotional state, concentration, and athletic performance of cybathletes during the preparation stages and during competitions. Methods and structure of the study. To achieve this goal, the following methods were used: analysis and synthesis of specialized scientific and methodological literature; observation of the cybathletes’ behavior and reactions; application of the anxiety assessment method of Ch.D. Spielberger and Yu.L. Khanin; statistical analysis of the obtained data. The study was conducted on the basis of two sporting events: the VII Martial Arts and Strength Sports Festival in Honor of Grand Duke Dmitry Donskoy (October 25–26, 2025, Suzdal) and the Cybathletics Festival, which was timed to coincide with Yaroslavl City Day 2025 (May 31, 2025). Thirty cybathletes participated in the study. The participants in the competition were individuals with disabilities who use technical rehabilitation equipment. Results and conclusions. The conducted study showed an improvement in the overall psychological state and an increase in the stability of the performance of cybathletes after the systematic use of elements of autogenic training in the preparation process. A decrease in the level of anxiety before competitions and an increase in concentration directly during the performance were noted. The findings of the study confirm that the use of autogenic training in the process of preparing cybathletes makes it possible to: increase the psychological resilience of cybathletes before competitions; ensure higher-quality exercise performance by stabilizing the emotional state of participants with disabilities; and optimize the process of athletic preparation, making it more effective.